ACADEMIC TRAINING IN MEDIA AND COMMUNICATION SCIENCES AND ITS RELATIONSHIP TO MEDIA PRACTICE:: (Reading In The Nature Of The Relationship: Integration Or Separation) - Hamdi, Mohamed El Fateh; Setoutah, Samira (ALBAHITH ALALAMI, 2019)
The aim of this scientific study is to diagnose the nature of the relationship between academic education in the field of media, communication and media practice. The university offers theoretical and practical lessons to students on the concepts of communication sciences, theories, models, legislations, ethics, and techniques over three years or more. And the diploma in the field of communication and Media Sciences gives students the opportunity to work in the field of journalism and media in the future, this is what many academics and media thinkers in Algeria believe, while another trend sees the exact opposite: The study of information and communication sciences within the university in the form of theoretical lessons cannot contribute to the improvement and development of the level of the student who aspires to practice the profession of journalism. In this study, we will try to find out whether the academic experience in the field of media has a relationship with the media practice in the field, or that the professional practice in the field of journalism and the media requires other criteria and conditions that must be taken into account in the university stands.